The impact of e-commerce on small and medium-sized enterprises (SMEs) in Malaysia - Ding Song; Kharmeyni Jumbulingam; Hossam Fadel; Ni Made Sumarningsih (Universitas Pendidikan Nasional, 2022)
This research set out to determine how e-commerce affects Malaysian SMEs and what reasons prevent more SMEs from adopting this business model. The conceptual framework and research hypotheses were developed after an extensive literature review. Two hundred and fifty Malaysian SME owners and managers were surveyed using a questionnaire, and the collected data was analyzed using descriptive and inferential statistics. The main results showed that the adoption of e-commerce among Malaysian SMEs is highly influenced by personal, technological, organizational, and environmental variables. Researchers concluded that personal characteristics were the most influential, followed by those related to the workplace and the surrounding environment. Together, these characteristics accounted for 56.5% of the variance in e-commerce adoption among Malaysian SMEs. Important implications for policymakers, researchers, and practitioners in Malaysia who want to encourage e-commerce acceptance and growth among SMEs were drawn from the results, which add to the current literature on e-commerce adoption in SMEs. The report concluded with suggestions for targeted interventions and support programs to increase the competitiveness and growth of small and medium-sized enterprises (SMEs) in Malaysia through e-commerce. The study's findings helped advance Malaysia's economy as a whole and ensure the digital sector continues to thrive.